Increasing Students’ Reading Comprehension Using Listen Read Discuss (LRD) of Recount Text - Dahler Dahler (ELT-Lectura, 2016)
In this research, researcher found that students had low in reading comprehension of recount text.Where, the students’ average score of reading comprehension in recount text was 60. It can not pass the standard minimum of school. This research is classroom action research. And the researcher used listen Read Discuss strategy to solve the students’ problem. The purpose of this research was to solve students’ problem in reading comprehension of recount text. This research was done in two cycle, and the result of analysis showed that the average score of the students based score was 60. The average score of the students in cycle I was 77, although the students’ average have been improved, the researcher conducted cycle II. It because there is one indicator that could not pass the passing grade. And students’ average in cycle II was 83. It had improvement 23 points from based score to cycle II. And the researcher concluded that applying Listen Read Discuss strategy could better to solve students’ reading comprehension problem in recount text.